Pengembangan Kemampuan Penyusunan Best Practice Guru PAI Melalui Final Product Based Learning Techniques - Aminah, Siti; Hardani; Purwaminanda, Miftahuddin Ahmad (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2023)
The professional competence of teachers in compiling Best Practice scientific papers still needs to improve, so efforts are required to enhance it, including through the implementation of E-Short Course Best Practice. The purpose of this writing is to describe the success of implementing the E-Short Course Best Practice in improving the ability to write Best Practice papers using Final Product Learning Techniques for teachers and supervisors of Islamic Religious Education at the Office of the Ministry of Religion, Sleman Regency, Special Region of Yogyakarta organized by Semarang Religious Education and Training Center in 2022. The method used in this study is an evaluation research method. The research results showed that the ability of all substances and their respective aspects was increasing. The final product revision stage revealed enhancement in all senses and elements between 7 people (17.5%) and 12 (30%). As for the development of the final product assessment with excellent criteria, the highest was in inspirational substance, in the D8 aspect (the topic of discussion giving inspiration to other teachers), a total of 12 people (30%). In contrast, the result of the final product assessment was perfect, with the lowest achievement in innovation substance in aspect B3 (Results achieved related to improving the quality of learning) and inspirational meaning in aspect D9 (Topics of discussion inspire policy makers) a total of 6 people (15%). The conclusion shows an enhancement in the ability to write best practice papers for teachers and supervisors of Islamic religious education after participating in the best practice e-short course using final Product-based Learning techniques.(Kompetensi profesional guru dalam menyusun karya tulis ilmiah Best Practice masih rendah, sehingga diperlukan upaya untuk meningkatkannya, diantaranya melalui pelaksanaan E-Short Course Best Practice. Tujuan penulisan karya tulis ini adalah untuk mendeskripsikan keberhasilan pelaksanaan E-Short Course Best Practice dalam meningkatkan kemampuan menyusun karya tulis Best Practice dengan menggunakan Final Product Based Learning Techniques bagi guru dan pengawas Pendidikan Agama Islam pada Kantor Kementerian Agama Kabupaten Sleman Daerah Istimewa Yogyakarta yang diselenggarakan oleh Balai Diklat Keagamaan Semarang tahun 2022. Metode yang digunakan dalam penelitian ini adalah metode penelitian evaluasi. Hasil Penelitian menunjukkan bahwa terjadi peningkatan kemampuan pada semua substansi dan aspek masing-masing. Capaian hasil pada tahap revisi produk akhir diketahui terjadi peningkatan pada semua substansi dan aspek masing-masing antara 7 orang (17.5%) hingga 12 orang (30%). Adapun capaian hasil penilaian produk akhir dengan kriteria amat baik paling tinggi pada substansi inspiratif, pada aspek D8 (Topik bahasan memberikan inspirasi kepada guru lain) sejumlah 12 orang (30%). Sedangkan capaian hasil penilaian produk akhir dengan kriteria amat baik dengan capaian paling rendah ada pada substansi inovasi pada aspek B3 (Hasil yang dicapai berkaitan dengan peningkatan kualitas pembelajaran) dan substansi inspiratif pada aspek D9 (Topik bahasan memberikan inspirasi terhadap pembuat kebijakan) sejumlah 6 orang (15%). Kesimpulan menunjukkan bahwa terjadi peningkatan kemampuan menyusun karya tulis Best Practice pada guru dan Pengawas Pendidikan Agama Islam setelah mengikuti E-Short Course Best Practice dengan menggunakan Final Product Based Learning Techniques.)